Efeito in situ da aplicação de pastas de CPP-ACP e CPP-ACPF previamente a um desafio erosivo de curta duração - Fernandes, Liege Helena Freitas (2017)
Dental erosion has been highlighted by the increase of its prevalence, which has mainly occurred due to a changing in eating habits and in the modern society lifestyle. Different therapeutic approaches have been evaluated as potential alternatives in their control among which is the use of casein phosphopeptide - amorphous calcium phosphate (CPP-ACP). The available studies in the literature with pastes containing CPP-ACP, associated or not to fluoride (CPP-ACPF) have shown conflicting results. Thus, the present work evaluated the inhibitory potential of erosive demineralization of CPP-ACP pastes by a short-term in situ protocol. For this, twelve volunteers used palatal intraoral devices containing four specimens of bovine enamel. The 192 enamel specimens had their initial superficial hardness (SHi) measured and were randomized between the volunteers and study groups. The experimental groups were: GI = Paste of CPP-ACP (MI Paste ™), GII = Paste of CPP-ACPF (MI Paste Plus ™), GIII = Fluorinated Paste (900 ppm NaF) and GIV = placebo paste. At each stage of the study, after the formation of the acquired film (two hours of continuous use), the volunteers did the intrabuccal application of the paste (three min) and used the intrabuccal device for three additional hours. The erosive lesion was then produced by immersing the intraoral device for 30 seconds in 150 ml of hydrochloric acid (0.01M, pH 2.3). The four cross-steps were intercalated with a 1-day washout period and the final surface hardness (SHf) was measured for the calculation of the percentage of hardness loss (%SHL). The data were analyzed by ANOVA for repeated measurements and Tukey's test (α = 5%) using SigmaPlot software. The results of the hardness loss showed differences between the groups (p <0.05). CPP-ACP and CPP-ACPF pastes showed a significantly lower percentage of hardness loss (9.26% and 9.14%, respectively) than the fluoridated paste (15.5%) and placebo (16.7%), but without differences between them. It was concluded that CPP-ACP pastes were able to reduce erosive demineralization compared to fluoridated paste and placebo, but the incorporation of fluoride in its formulation did not promote additional benefit.